Exploring the Synergistic Influences of Clay Nanoplatelets and Waste Eggshell Particles on PMMA-Based Hybrid Nanocomposites - Hamad, Sameer F.; Abd, Aya Waleed; Al-Obaidi, Anwer J.; Abdulridha, Nazar J. (Engineering Transactions, 2026)
This study investigates the impact of incorporating clay nanoplatelets and waste eggshell particles into poly(methyl methacrylate) (PMMA) to develop hybrid nanocomposites with improved mechanical and structural properties. Waste eggshells, rich in biogenic calcium carbonate, were utilized as a sustainable, low-cost filler, while clay nanoplatelets provided nanoscale reinforcement and improved interfacial bonding. The hybrid nanocomposites were prepared at a filler content of 5 % (hereafter designated as 5 wt.%) using the solution casting method. Scanning electron microscopy (SEM) was employed to examine the dispersion and morphologyof the fillers within the structure of the PMMA matrix. At the same time, Fourier-transform infrared spectroscopy (FTIR) was utilized to assess the powder chemical interactions and potential bonding between the fillers (clay nanoplatelets and eggshell particles) and the PMMA matrix. The mechanical behavior of the PMMA and the produced hybrid nanocomposites was also evaluated through tensile testing. The results indicate a synergistic enhancement due to the combination of organic biowaste and inorganic nanoclay, offering a promising route for the development of sustainable, high-performance polymer nanocomposites.